Association of mortality rates and availability of emergency and specialized, including high-tech, medical services for acute coronary syndrome in the Russian Federation - B. A. Oleynik; V. I. Starodubov; V. A. Evdakov; L. R. Abzalilova (Российский кардиологический журнал)
Aim. To study the impact of the availability of emergency and specialized, including high-tech, medical services for patients with acute coronary syndrome on mortality in Russia.Material and methods. We used the cointegration of time series characterizing mortality from acute coronary syndrome (ACS) and following parameters for the availability of emergency and specialized, including high-tech, care for ACS in Russia for the period from 2016 to 2021 according to the "Monitoring of interventions to reduce mortality from coronary artery disease": the proportion of ambulance visits for ACS with response time <20 minutes; the proportion of patients with ST-elevation ACS (STE-ACS) hospitalized within 12 hours from symptom onset; proportion of patients with STE-ACS admitted to hospital within 2 hours of symptom onset; proportion of patients with ACS admitted to specialized departments; proportion of patients with STE-ACS with prehospital thrombolysis; proportion of patients with STE-ACS with thrombolysis; proportion of patients with STE-ACS who underwent percutaneous coronary intervention (PCI); proportion of patients with non-ST-elevation ACS (NSTE-ACS) who underwent PCI; the proportion of patients with STE-ACS admitted before 12 hours from the onset of symptoms who underwent PCI; proportion of patients with ACS who underwent coronary artery bypass grafting. To rank the availability indicators, the elasticity (E) coefficient was used, which characterizes the strength of the relationship between the factor and the result, which shows the change in the result value per 1% change in the factor.Results. According to contribution decrement to reducing mortality, the factors of health care availibility for patients with ACS-STE were arranged as follows (coefficient of elasticity and determination (R2) is indicated in brackets): "The proportion of patients with ACS-STE who underwent PCI" (E=1,5%; R2=0,60), "Proportion of patients with STE-ACS with prehospital thrombolysis" (E=1,1%; R2=0,91), "Proportion of patients with STE-ACS with thrombolysis" (E=1,0%; R2=0,96 ), "Proportion of patients with STE-ACS admitted before 12 h who underwent PCI" (E=0,9%; R2=0,94), "Proportion of patients with STE-ACS admitted to hospital before 12 h from the symptom onset" (E=0,5%; R2=0,97), "Proportion of patients with STE-ACS hospitalized <2 hours from the symptom onset" (E=0,2%; R2=0,95). A significant resource in reducing mortality in ACS is the reduction in ambulance response time in ACS (E=2,3%; R2=0,87) and compliance with specialized hospitalization of patients with ACS (E=1,8%; R2=0,73), but in reducing mortality in NSTE-ACS, the proportion of patients with NSTE-ACS who underwent PCI (E=1,7%; R2=0,72).Conclusion. An analysis of the impact of the availability of emergency and specialized, including high-tech, medical services for patients with ACS in Russia showed that the greatest contribution to mortality reduction in STE-ACS is made by time reduction in PCI and an increase in the use of thrombolytic therapy, mainly at the prehospital stage, in NSTE-ACS — an increase in the number of PCIs, and in ACS in general, strict compliance with specialized hospitalization of patients and a reduction in ambulance response time in ACS.